Evaluating Systems Pharmacology Models Is Different From Evaluating Standard Pharmacokinetic–Pharmacodynamic Models. (19th February 2014) - Agoram, B
Abstract : Based on the author's recent experience, there appears to be some confusion regarding the steps required to qualify a systems pharmacology model as adequate for the intended purpose. This manuscript outlines the model evaluation approach used in the author's recent publication 1 on the systems pharmacology of a 5‐lipoxygenase inhibitor and is an attempt to generate discussion on this topic within the pharmacometrics and systems pharmacology community. CPT Pharmacometrics Syst. Pharmacol . (2014) 3, e101; doi:10.1038/psp.2013.77 ; published online 19 February 2014